2020
DOI: 10.4314/bajopas.v12i1.28s
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat dichloride adsorption from aqueous solution using Carbonized Bambara Groundnut (<I>Vigna subterranean</I>) Shells

Abstract: Carbonized Bambara GroundNut Shell (CBGNS) was used as adsorbent for the adsorption of paraquat dichloride (PQ) from aqueous solution. The prepared adsorbent was characterized using scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy methods. Several parameters that might affect the adsorption process including pH, contact time, adsorbent dosage, temperature and initial concentration were investigated and optimized using batch adsorption technique. Results of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The results showed that the adsorbent exhibited good adsorptive properties for removing anionic dyes from aqueous solution owing to its low moisture content, high pore volume, and bulk density. Ayuba and Thomas (2021) reported similar results when they used carbonized Bambara groundnut (Vigra subterranean) shells to remove Paraquat dichloride from aqueous solution. Figure 2 shows the graph of the point of zero charge (PZC) for UTG adsorbent.…”
Section: Adsorbent Characterizationmentioning
confidence: 71%
“…The results showed that the adsorbent exhibited good adsorptive properties for removing anionic dyes from aqueous solution owing to its low moisture content, high pore volume, and bulk density. Ayuba and Thomas (2021) reported similar results when they used carbonized Bambara groundnut (Vigra subterranean) shells to remove Paraquat dichloride from aqueous solution. Figure 2 shows the graph of the point of zero charge (PZC) for UTG adsorbent.…”
Section: Adsorbent Characterizationmentioning
confidence: 71%
“…Pore (Void) Volume Determination. To determine the pore volume of the adsorbents, the method reported by [20] was adopted. 2.0 g of the samples (RWL, CWL and AWL) was immersed in water and boiled for 15 min.…”
Section: Sample Collection and Adsorbent Preparationmentioning
confidence: 99%
“…where the constant kint (mg/min.) is the intraparticle diffusion constant ratio, and C is the boundary layer thickness [20].…”
Section: The Kinetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Additionally, it serves as a low-cost source of high-quality protein. Leveraging Bambara shell as a natural, costeffective, safe, and environmentally friendly alternative, it offers promising potential for conventional remediation systems 16 Lignin, extracted from agricultural residues, exhibits notable adsorption capacity and a strong affinity for removing heavy metal. 17,18 Consequently, 16 investigated carbonized Bambara groundnut shell as an adsorbent for removal of paraquat dichloride from aqueous solution.…”
Section: Introductionmentioning
confidence: 99%